(untitled) (LACCEI, 2024)
Livestock is one of the most important activities, however, it contributes to global warming, becoming one of the major sources of methane emissions. It should be taken into account that diet manipulation is one of the efficient alternatives that allows modifying ruminal fermentation, improving nutrient assimilation and, therefore, reducing methane. Therefore, in this systematic review, the efficacy of nutritional strategies for the reduction of methane gas emissions in cattle was determined through the compilation of research journals published in scientific databases in the last 10 years. Information from undergraduate, master’s and doctoral theses and articles from journals indexed in Scopus, Dialnet, Redalyc, Science Direct considering the period 2012-2022 and the Spanish, English and Portuguese languages was used. As a result, it was obtained that the variation of methane emissions is related to the amount of feed ingested and the quality, defined by digestibility and fiber content. It is concluded that sunflower oil, linseed oil, starch oil and Leucaena leucocephala present an efficiency of 21.5%, 38%, 12.8% and 61% respectively in reducing enteric CH4 emission.